2020
DOI: 10.1101/2020.09.22.308411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Actuation Enhances Patterning in Human Neural Tube Organoids

Abstract: Tissues achieve their complex spatial organization through an interplay between gene regulatory networks, cell-cell communication, and physical interactions mediated by mechanical forces. Current strategies to generate in-vitro tissues have largely failed to implement such active, dynamically coordinated mechanical manipulations, relying instead on extracellular matrices which respond to, rather than impose mechanical forces. Here we develop devices that enable the actuation of organoids. We show that active m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…However, other factors may also need to be considered. For example, a recent study has shown that mechanical force of culture environment can also affect neural tube organoids growth and patterning 73 . All these three improvements will make neural tube organoids more reliable and more similar to the in vivo neural tube.…”
Section: Potential Development and Applications Of Neural Tube Organoidsmentioning
confidence: 99%
“…However, other factors may also need to be considered. For example, a recent study has shown that mechanical force of culture environment can also affect neural tube organoids growth and patterning 73 . All these three improvements will make neural tube organoids more reliable and more similar to the in vivo neural tube.…”
Section: Potential Development and Applications Of Neural Tube Organoidsmentioning
confidence: 99%
“…Organoids have often been used as simplified models of patterning and have allowed insight into the underlying biochemical [41][42][43][44] and mechanical 1,20,45,46 factors that control cell fate specification and morphogenesis. We and others have shown that NTOs display patterned FPs 9,11,12,20 which emerge, remarkably, despite the lack of the notochord, which in vivo acts as a spatial reference frame for FP patterning 28,47,48 through the secretion of SHH morphogens. This suggests that in vitro epithelial patterning follows mechanisms that might differ from those employed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify the inhibitor species in the hNTO system, we performed receptor-ligand interaction analysis 31 on an scRNAseq dataset obtained from dissociated hNTOs at day 5, corresponding to hNTOs after RA-SAG exposure but before FP induction, and at day 11, after FP induction and patterning 20 .…”
Section: Receptor-ligand Interaction Analysis Reveals Wnt As Putativementioning
confidence: 99%
“…Anteroposterior and dorsoventral identity could be modulated by the activation of retinoic acid or sonic hedgehog signaling ( Ranga et al, 2016 ). In addition, morphogenetic changes inducing neural tube closure were mimicked in vitro , which improved neural differentiation and patterning of NTOs derived from hPSCs ( Fattah et al, 2020 ; Figure 2 ).…”
Section: Recapitulating Selected Developmental Trajectories In Vitromentioning
confidence: 99%